2022
DOI: 10.1039/d1tb02306c
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic smart nanoplatform for dual imaging-guided synergistic cancer therapy

Abstract: Developing an integrated multimodal diagnosis and therapeutics nanoplatform is of great importance to enhance the cancer therapy outcome. Herein, we report a highly efficient and biocompatible nanoplatform based on the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Erythrocyte membrane (EM) vesicles were obtained according to the previous methods with some modification [ 24 ]. Firstly, erythrocytes were collected from BALB/c mice fresh blood and washed with PBS for several times to remove plasma and unwanted cells until the supernatant became colorless.…”
Section: Methodsmentioning
confidence: 99%
“…Erythrocyte membrane (EM) vesicles were obtained according to the previous methods with some modification [ 24 ]. Firstly, erythrocytes were collected from BALB/c mice fresh blood and washed with PBS for several times to remove plasma and unwanted cells until the supernatant became colorless.…”
Section: Methodsmentioning
confidence: 99%
“…Successful application of magnetically responsive nanoplatforms includes encapsulation/immobilization of therapeutic agents into magnetic-responsive nanoplatforms, injection of the magnetic stimuli-responsive nanoplatforms into the body and taking advantage of external magnetic fields to recruit and activate the magnetic stimuli-responsive nanoplatforms at the lesions of interest [ 384 386 ]. Recently, Shuai et al [ 387 ] reported a GSH-responsive MOF to effectively load IDO inhibitor, and NO donor s-nitrosothiol groups for improving antitumor immunotherapy.…”
Section: Stimuli-responsive Targeting Strategiesmentioning
confidence: 99%
“…207 In recent years, there have been numerous reports of porphyrin MOF-targeted delivery of DOX for synergistic therapy. [208][209][210] In order to prevent drug leakage during targeted chemotherapy, mitigate the side effects of the treatment and improve the drug loading rate, Zhao and coworkers designed a ZnO-gated porphyrinic MOF (porMOF)-targeted PDT/chemotherapy system. 211 As shown in Fig.…”
Section: Targeted Applications Of Chemotherapymentioning
confidence: 99%